Novas contribuições ao modelo de fragilidade ambiental a processos erosivos : estudo de caso aplicado ao perímetro urbano de Rondonópolis, Mato Grosso - Guirra, Alesson Pires Maciel (2017)
This study applied to the urban perimeter of Rondonópolis-MT, brings new adaptations and complements to the methodologies and consequently to the models of environmental fragilities to erosive processes, especially those carried out in urbanized areas or with tendencies to urbanization. The classes and degrees of the environmental fragilities associated to each type of geoenvironmental variable were evaluated: relief (slope and terrain forms), erodibility of soil orders considering the effects of urbanization, climatic elements of rainfall (rainfall intensity and erosivity ), geological-structural features of the groups of rocks (mechanical resistance to erosion, density of geological-structural discontinuities and density of these intersections), being possible to characterize the potential environmental fragilities of this territory. Combining these variables with the model of environmental fragilities associated to the levels of urbanization and degree of protection and soil cover, we obtained the emerging environmental fragilities. It was verified that to the proposed analysis model, integrating new geoenvironmental variables, indispensable to the holistic diagnosis of urban-environmental systems, characterized in a more coherent way the loss of material by linear erosion in the current scenario, serving as support to the environmental zoning of the Master Plan of this municipality.